Sztuczna inteligencja a inteligencja moralna. Zagadnienia wstępne cybernetyki - Szulczewski, Grzegorz (Annales. Etyka w Życiu Gospodarczym, 2019)
We live in a time when artificial intelligence is being used in more and more areas of our lives. Its use in the sphere of management has become a big problem. Should we comply with the judgments of the cold rationality of artificial intelligence or, by contrast, are we able to realize the limits of its application? The question should be asked: why can good management not be limited to solutions presented by artificial intelligence? In order to answer this question, one should show what the difference is between artificial intelligence and moral intelligence, and what the use of moral intelligence in management is. The role of ethics in the decision-making process will be shown. The final conclusion is that artificial intelligence will never replace man in management.